"Real space is experience space": David Antin's philosophy of photography. (2nd January 2022) - Evans, Ariel
Abstract : This article surveys poet David Antin's ideas about photography at the turn of the 1970s. Then-new Chair of the Visual Arts Department at the University of California, San Diego, Antin shepherded the department's now-landmark photography program while also experimenting with photography himself as a medium for his philosophy and poetry. Closely reading the cover of Antin's poetry book Talking (1972), I consider how Antin used photography to represent "real space" — to Antin, the pulse and texture of thinking and talking, its shifts and pauses in response to internal and environmental stimuli. Setting Talking alongside Antin's critical essays of the same years, I argue that Antin was working toward an art of conversation; specifically, an attention to artist-audience relationships. I also suggest that Antin's interest in representing the conversational offered an influential theory of photography that Antin's mentees Martha Rosler and Allan Sekula (among others) elaborated in their landmark "reinvention of documentary" of the late 1970s-early 1980s .